THE IMPACT OF EMPLOYING COMPOUND EXERCISES WITH AN INTENSITY DISTRIBUTION APPROACH ON CERTAIN ASPECTS OF STRENGTH AND ITS RELATIONSHIP TO SHOOTING ACCURACY AMONG YOUNG HANDBALL PLAYERS - T. A. Firas Qahtan Rajab; Prof.Dr. Rachid Sakly (Galaxy International Interdisciplinary Research Journal, 2023)
The remarkable progress observed in various sports worldwide is undoubtedly attributed to coaches adopting sound scientific principles of sports training, keeping abreast of developments, and actively seeking to discover more training methods. The current study aims to investigate the impact of utilizing compound exercises with an intensity distribution approach on the development of muscle strength and shooting accuracy among young handball players.